Country-Religious Relations: Building Power in the Path of Paradox - Nurus Shalihin; Nazif Hidayatullah (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study aims to describe the relationship between state and religion due to polarization and identity politics during Joko Widodo's leadership in Indonesia. The data in this study were collected through media coverage of political events related to religion from 2014 to 2019. The media that became the data source were the online news portals Kompas.com, Tempo.com, Detik.com. The three online news portals were chosen on the basis of their existence being verified and on a national scale. Data were analyzed in four stages; data management, data memoing, description-classification-data interpretation and data visualization. This study finds that the relationship between the state and religion has entered a paradoxical relationship phase, which is indicated by various contradictory policies. This paradox was deliberately built by President Joko Widodo as a way and strategy to build a fantasy of power.